Faktor-faktor yang Mempengaruhi Financial Distress pada Perusahaan Pertambangan yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2019 - Sully Kemala Octisari; Retno Asih; Tunggul Priyatama (Majalah Imiah Manajemen & Bisnis, 2022)
This study aims to examine the effect of liquidity, leverage, operating capacity, and firm size on financial distress. The population in this study were 43 mining companies listed on the Indonesia Stock Exchange for the period 2016-2019. By using purposive sampling, a sample of 12 companies was obtained with a research period of 4 years, resulting in 48 data. The data in this study are secondary data in the form of annual financial reports. The method of analysis in this study is panel data regression analysis using Eviews 9 software. The results of the partial significance test show that liquidity, leverage and firm size have a significant positive effect on financial distress, while the operating capacity variable has a significant negative effect on financial distress.